Double diffusive dissolution model of UO2 pellet in molten Zr cladding. Issue 4 (3rd April 2023) - Itoh, Ayumi; Yamashita, Susumu; Tasaki, Yudai; Kakiuchi, Kazuo; Kobayashi, Yoshinao
ABSTRACT: The rapid dissolution of UO2 in molten Zr that could occur during fuel-cladding liquefaction at high temperatures and its kinetics were reformulated considering the convective mass transfer and the scouring effect at the UO2 /Zr interface. The mass transfer coefficient of U was obtained as a correlation including the aspect ratio term by computational fluid dynamics (CFD) analysis. To explain the gap between the rapid dissolution rate observed in the experiments and the density-driven convective mass transfer, we introduced an idea in which the eutectic melting at the UO2 /Zr interface promotes the solid oxide detachment owing to infiltration of the U-Zr-O liquid into the UO2 grain boundaries (scouring effect). The developed model was validated with UO2 -Zr crucible experiments at 2273 and 2373 K. The calculated mass percentage ratios of U/Zr agreed with the measurements, and the transition timings from rapid dissolution stage were consistent with the metallographic observations. Graphical Abstract: uf0001